BILINGUAL (CLIL) TEACHING IN THE SERBIAN EDUCATION SYSTEM: CURRENT CHALLENGES AND PROPOSED GUIDELINES FOR THE FUTURE (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
The subject of the paper is a description of the current organization of bilingual teaching in the educational system of the Republic of Serbia with separate challenges facing students and teachers in a given teaching context. The paper presents the content of the Rulebook on closer conditions for bilingual teaching with special reference to the missing elements of the document such as: teacher training, use of textbooks, criteria for student assessment and the structure of the final (graduation) exam at the end of high school cycle. Based on the analysis of the mentioned aspects in the European practice of CLIL teaching, guidelines for further development of bilingual teaching in the Republic of Serbia are proposed, with special reference to the elements that are missing in the given educational system.
Keywords: CLIL bilingual teaching; teacher training; textbooks; evaluation; final (graduation) exam